ENDOSCOPIC CARTILAGE TYMPANOPLASTY. OUR TECHNIQUE AND EXPERIENCE OF 157 CASES - Najam, Muhammad Atif; Sarwar, Urwa; Raza, Maqbool; Khan, Khalid Azam; Saleem, Humaira; Niazi, Najm u Saqib; Rashid, Muhammad; Riaz, Naeem (Pakistan Armed Forces Medical Journal, 2021)
Objective: To assess the graft take rate and hearing gain in trans-canal endoscopic tympanoplasty Study Design: Descriptive study. Place and Duration of Study: Pakistan Naval Ship Hafeez, Islamabad Pakistan, form Dec 2015 to Jun 2018 Methodology: All patients with dry central perforations of >3 months history were included in the study. All Patients with perforations of pars tensa were booked for endoscopic cartilage tympanoplasty. All perforations were divided into four types small, medium, large and subtotal or total based on size of the tympanic membrane perforations. Small perforations involving <25% area of Pars Tensa. Medium perforation are Perforations involving 25-50% of Tympanic membrane. Large perforations include Perforations involving 50-75% of pars tensa. Subtotal or total perforations are defined as perforations with >75% perforation of the tympanic membranes. Wet Ears and perforations involving the Pars Flacida were excluded from the study. Preoperative Audiogram was carried out for all patients and A-B Gap were noted for all groups separately so as the demographic data including age and gender. Success was defined as complete closure of Tympanic membrane perforation at 3 months. All patients were operated with 0 Degree 3mm, 14cm rigid endoscope under general anesthesia. Results: Mean age of patients was. 37 years and standard deviation was 12.34 (range 12-58 years). Out of total 157 cases 81 patients male were males (51%) and 76 patients were females (49). Out of 157 ears operated 146 Perforations healed completely an overall success rate of 92%. Patients with small perforations had 100 percent success.....